1992
DOI: 10.1002/ijc.2910500409
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection in esophageal squamous‐cell carcinoma in western countries

Abstract: Recent studies have suggested that esophageal HPV infection could be a risk factor for esophageal squamous-cell carcinoma. The aims of our study were to assess the presence of HPV esophageal infection among French patients with esophageal squamous-cell carcinoma and to compare the prevalence of this infection among control patients exposed to similar known risk factors (alcohol and tobacco) and among non-exposed control patients. All patients had the following investigations: serum immunoglobulin level, T-lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…71 72 Divergent results were reported; no HPV DNA was detected in the 37 cases analysed from Hong Kong, 71 whereas 42% of cases were positive in a series collected from France. 72 This last figure is consistent with the results from Chinese patients examined by means of SBH (table 1) [73][74][75][76] In situ hybridisation Until now, 13 studies have been published on the detection of HPV in oesophageal carcinomas using ISH. 11 46 63 72 77-84 The numbers of patients in these studies have been relatively small, except for the study reported by Chang et al, which comprised 363 cases, 78 and another by the same authors, which comprised a total of 700 patients from the high incidence area of China (table 1).…”
Section: Filter In Situ Hybridisationsupporting
confidence: 85%
“…71 72 Divergent results were reported; no HPV DNA was detected in the 37 cases analysed from Hong Kong, 71 whereas 42% of cases were positive in a series collected from France. 72 This last figure is consistent with the results from Chinese patients examined by means of SBH (table 1) [73][74][75][76] In situ hybridisation Until now, 13 studies have been published on the detection of HPV in oesophageal carcinomas using ISH. 11 46 63 72 77-84 The numbers of patients in these studies have been relatively small, except for the study reported by Chang et al, which comprised 363 cases, 78 and another by the same authors, which comprised a total of 700 patients from the high incidence area of China (table 1).…”
Section: Filter In Situ Hybridisationsupporting
confidence: 85%
“…Interestingly, a much lower HPV infection rate of 4.3% has recently been reported in ESCC collected from Peking, China, which has a lower risk of esophageal cancers (Suzuk et al, 1996). Worldwide, the incidence of HPV infection is highly variable, ranging from 0% in The Netherlands (Smits et al, 1995) to 42% in France (Benamouzig et al, 1992). There appears to be a tendency for a lower detection rate of HPV infection in geographic regions with a low incidence rate of esophageal cancers.…”
Section: Relationship Between Hpv Infection and P53 Mutationmentioning
confidence: 99%
“…In another study the HPVs frequencies in ESCC were as follows: HPV-16, 54.7%; HPV-18, 4.8%; HPV-6, 14.3%; HPV-66, 7.1%; HPV-52, 4.8%; and 14.3% of cases were positive for more than 1 type of HPV [47]. In France 5 out of 12 patients with oesophageal carcinoma had HPV oesophageal infection and the most frequently observed types are HPV 16/18; thus HPV infection may be implicated in the development of ESCC in association with known risk factors [48]. In other Western countries the results show that, in contrast to geographic regions where ESCC is prevalent, HPV infection occurs infrequently in association with ESCC [49].Our results are consistent with HPV DNA studies conducted in other high-risk areas for ESCC which showed evidence of HPV in tumour tissues from 20% to 50% of ESCC cases and provided further evidence to support a causal association of HPV infection with oesophageal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 98%